Mapeamento das dissertações e teses da Pós-graduação em Psicologia da UFMG. - Maria Clarice Lima Batista (2024)
Dissertations and theses, in addition to being a prerequisite for obtaining a degree, are the result of the stages of scientific work in the postgraduate student's academic career and consolidate the student's training as a researcher. This highlights the importance of this type of scientific production in the excellence of postgraduate programs and leads us to the need to look at the actors who occupy these spaces: graduates, advisors, co-supervisors and partner institutions. This scientometric study, using bibliometric tools, analyzes the dissertations and theses of the Psychology Graduate Program at UFMG, in order to contribute to a better understanding and improvement of the trajectory of the programs and their areas of concentration. An alternative format was adopted, a Thesis in Multiple Studies, structured in 03 separate studies that are interconnected, which is suitable for individualizing the analysis of each PPG and its Areas of Concentration, without losing the whole to which they are linked, which is UFMG's stricto sensu Psychology. The corpus analyzed consists of 571 graduated, the supervising and co-supervisors present in the two programs, PPG-PSI and PPG-COGCOM, in the Master's and Doctorate, from 2012 to 2022. The total production generated consists of 571 works: 405 dissertations and 166 theses defended in the period. The analysis allowed us to obtain, for each Area of each Program, the academic production, the distribution of defenses by Supervisor, by Concentration Area, and the occurrence of Co-supervision in the research. The contribution to the interdisciplinarity of the Programs was obtained by the Research Area and Institution of origin of the Co-supervisor and the doctoral student based on their academic origin in their Master's degree. Aspects relating to internationalization were obtained from the institutional origins of the Co-supervisors and the foreign institutions of the doctoral students' Master's degrees. Endogenous and exogenous aspects were identified based the presence of institutions and external areas in interaction. This study aims to provide, in addition to a characterization of the Program and the actors involved, a stimulus for reflection on how the Psychology Graduate Program at UFMG wants to be recognized, as well as to stimulate new research in the chain of Academic Guidance, based on Graduates, Advisors and Co-supervisors, contributing to the improvement of the Program, The Psychology Area and evaluations by CAPES.